From coastal material to relational sound: rethinking organology through the SUKABACA aerophone in Maluku - Nelsano A Latupeirissa; Ronaldo B Alfons (Gelar: Jurnal Seni Budaya, 2026)
This study examines the transformation of the coastal plant papaceda (Scaevola taccada) into the aerophone instrument SUKABACA in Maluku, Indonesia, as an organological process based on local material. While traditional organology has focused on the classification and structural aspects of musical instruments, this research proposes a relational perspective that considers the interaction between material, structure, and musical practice. This study employs a qualitative approach with a practice-based research orientation, integrating instrument-making processes with acoustic analysis and performance evaluation. Data were collected through field observation, interviews, documentation, and organological experimentation, including material selection, instrument construction, and acoustic testing using a digital tuner. The findings show that the acoustic characteristics of SUKABACA are not solely determined by its structural configuration but are significantly influenced by the ecological properties of papaceda material and the performer’s technique. The non-homogeneous structure of the material contributes to variable pitch stability and timbral characteristics, indicating that sound production emerges from the interaction between material properties and performative practice. This study contributes to the development of organology by proposing a local material-based approach, positioning material as an active agent in shaping sound and musical innovation. This perspective expands organological studies from classification toward a relational understanding of musical instruments within ecological and cultural contexts.